Commented floristic listo f wild vascular plants in San Juan Quetzalcoapan, Tlaxcala, Mexico - Vibrans, Heike (Instituto de Ecología, A.C., 1997)
A checklist of 15 species of pteridophytes as well as of 381 spermatophytes is presented. The wildgrowing plants were collected between 1981 and 1993 for a study of the flora and vegetation of an area of about 9 km2 on the northern side of La Malinche volcano. The study area consists of the mestizo village of San Juan Quetzalcoapan, municipio of Tzompantepec, and its surroundings (2500 m above sea level). The main occupation is agriculture based on rain-fed maize cultivation. The checklist includes the following information: scientific name, name used locally, general distribution of the species, its habitat in the study area, observations on its frequency and uses, collection numbers and dates as well as commentaries. This report contributes to the inventory of the flora of a federal state not very well known up to now. It also shows that even the vegetation of very disturbed areas in Mexico can possess a considerable biological diversity.